Empowering Parents through Active Learning: Rethinking Evaluation in Elementary Education - Farhin, Nurul (International Journal of Active Learning, 2025)
This article discusses the importance of the role of parents in the process of evaluating education in elementary schools. With a collaborative approach between parents and educators, evaluation can be a more effective tool to improve student learning outcomes. This study presents practical strategies and models of parental involvement that can be implemented in the context of education. Education is one of the determining factors for changes in the quality of life in society. Education can produce citizens who have knowledge. In the process of education, teachers do not stand alone. In realizing the mission of learning, teachers need the role of parents as evaluators of education, especially at the elementary school level. Teachers need to communicate with parents to realize the achievement of education that is on the side of students. This study aims to analyze the importance of parental involvement in the transformation of evaluation in the context of elementary education.